Faktor-Faktor Pendukung Dibentuknya Kawasan Objek Wisata Huta Bolon Di Simanindo Sangkal Melalui Pendekatan Kearifan Lokal - Melly Andriana; Zuraidah Tharo; Ramayana Ramayana (Universitas Medan Area, 2022)
In the formation of the area into a tourist attraction, factors are needed in its favor. With the approach of local wisdom, it becomes a very important factor because it can be ascertained that each region has a very distinctive and unique culture or customs, as well as the architectural form of house buildings commonly called local wisdom. This research is very important to do as an effort to preserve the local culture that many young generations do not know about. To find out local wisdom, direct observation activities were carried out in Simanindo Sangkal Regency and several interviews were carried out with the surrounding community, as well as collecting data from several reliable sources related to local wisdom. Simanindo Sangkal is a village located in Samosir Regency, precisely on the shores of Lake Toba, North Sumatra. The results of this study show that (1) the number of gorga ornaments contained in each Bolon house, (2) There are meanings in each of the ornaments contained that are not only for homeowners but also for social communities, (3) The potential of the Huta Bolon Area has for the development of culture and the surrounding economy because it is close to Lake Toba which is one of the Geoparks in Indonesia.